THE EFFECTIVENES OF OUTING CLASS BASED CONTEXTUAL LEARNING ON UNDERSTANDING ENGLISH VOCABULARY IN JUNIOR HIGH SCHOOL LEVEL - Yuniar, Rendhi Fatrisna; Rozikin, Muhammad (English Edu: Journal of English Teaching and Learning, 2024)
The lexicon is a fundamental aspect that educators must focus on, as it encompasses all the words understood and used by an individual. The importance of an effective vocabulary program, which includes extensive reading, specific word instruction, independent word learning strategies, and word-play activities. Recent educational innovations, such as Outing Class Based Contextual Learning, aim to enhance students' vocabulary skills by incorporating real-life experiences into the learning process. Nawas (2018) highlights the benefits of the Contextual Teaching and Learning (CTL) approach in empowering students, fostering an interactive learning environment, and promoting collaboration. The primary focus of this study is to explore the implementation of class-based contextual learning strategies in order to enhance the comprehension of English vocabulary among junior high school students. The selection of this particular group is based on their active cognitive development, as outlined by Bujuri (2018). Employing a quantitative approach with a quasi-experimental design, the research involved two experimental groups: one receiving the treatment and the other serving as a comparison. The findings revealed significant improvements in the experimental group, with an average post-test score of 79,39, compared to the control group's score of 72.58. This disparity underscores the effectiveness of class-based contextual learning methods in enhancing the understanding of English vocabulary. From a practical standpoint, the aim of this research is to offer alternative teaching approaches to educators, enabling students to learn beyond the confines of the traditional classroom. This method proves highly effective in the current era, as it introduces a new learning environment, particularly in fostering enthusiasm for English vocabulary acquisition. Outing class-based learning offers the advantage of strengthening the relationship between subject matter and real-world contexts, thereby providing a more meaningful learning experience for students.